2019
DOI: 10.1177/1747519819866402
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of 3-O-substituted 1-benzyl-6-oxo-1,6-dihydropyridazine derivatives

Abstract: On the basis of 2-benzyl-6-hydroxypyridazin-3(2 H)-one, a series of its novel O-substituted (including 6-(1,3,5-triazin-2-yl)oxy) derivatives is prepared. It is proven that the substitution reactions in the initial compound occur mainly at the oxygen atom of the hydroxy group. On the basis of the obtained oxy-aceto(propane)hydrazides, the corresponding azides and anilides are synthesized. A series of 2-[(1-benzyl-6-oxo-1,6-dihydropyridazin-3-yl)oxy]- N′-(substituted benzylidene)aceto(propane)hydrazides is obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…2.2.1 General synthesis of intermediates. Intermediate 1 was synthesized using the experimental method reported in the literature, 40,41 taking 6-hydroxy-2-phenylpyridazin-3(2H)-one as an example. 1.00 g (6.92 mmol) of phenyl hydrazine hydrochloride was dissolved in 25 mL of secondary water, and heated to 90 1C until completely dissolved, then 0.75 g (7.61 mmol) of maleic anhydride was added, and 8 mL of dilute hydrochloric acid was added dropwise to the mixture, and was refluxed for 3 h. At the end of the reaction, cooled to room temperature, the mixture was poured into ice water to precipitate, left to stand, filtrated under reduced pressure and washed.…”
Section: Chemical Compound Synthesismentioning
confidence: 99%
“…2.2.1 General synthesis of intermediates. Intermediate 1 was synthesized using the experimental method reported in the literature, 40,41 taking 6-hydroxy-2-phenylpyridazin-3(2H)-one as an example. 1.00 g (6.92 mmol) of phenyl hydrazine hydrochloride was dissolved in 25 mL of secondary water, and heated to 90 1C until completely dissolved, then 0.75 g (7.61 mmol) of maleic anhydride was added, and 8 mL of dilute hydrochloric acid was added dropwise to the mixture, and was refluxed for 3 h. At the end of the reaction, cooled to room temperature, the mixture was poured into ice water to precipitate, left to stand, filtrated under reduced pressure and washed.…”
Section: Chemical Compound Synthesismentioning
confidence: 99%
“…The formed precipitate was filtered, washed with water and dried. 32 White solid, ( 0.43 g, 62%), m.p = 239-241°C. FT-IR ν (cm -1 ): 1091 (C=S),1155, 1342 (SO2), 1651 (C=N), 2939 (CH3), 1608 (C=C), 3321 (NH),3315 (NH ring).…”
Section: Synthesis Of N-[4-(5-mercapto-[134]thiadiazol-2-yl)-phenyl]-...mentioning
confidence: 99%
“…Studies of new hydrazine derivatives are ongoing, in which compounds with antimicrobial (Masunari and Tavaris, 2007, Loncle, et al, 2004, Küҫükgüzel, et al, 2003, Vicini, et al, 2002, anti-inflammatory (Todeschini, et al, 1998), anti-tuberculosis (Bijev, 2006), antitumor (Gürsoy and Ulusoy-Güzeldemirci, 2007), antimalarial (Gemma, et al, 2006), antidepressant (Ergenҫ, et al, 1998) and anticonvulsant (Ragavendran, et al, 2007) activities have been revealed. Some hydrazide derivatives, particularly, herbicides (benquinox, saijunmao, phenoxyaryl hydrazides of nicotinic acid) (http://www.alanwood.net/ pesticides/) and also the compounds with plant growth stimulating activity (Gomktsyan, et al, 2012, Yengoyan, et al, 2017, Pivazyan, et al, 2019, Shainova, 2019 are used in agriculture.…”
Section: A R T I C L E I N F Omentioning
confidence: 99%